Pemberdayaan Penyandang Disabilitas - Teguh Supriyanto; Rahmah Hidayat; Dadan Haryono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this research is to find out how the empowerment of persons with disabilities in the Social Service of Riau Islands Province. This study uses a qualitative method. Samples were taken using homogeneous sampling. Data analysis uses data collection, data collection techniques using the stages of observation, interviews, and documentation. The results of this study indicate that people with disabilities continue to face exclusion, discrimination, and various psychological disorders because they are not given the opportunity to advance in their careers and their rights and social service needs are not adequately met. ordered stakeholders in this case the government to change actions when implementing empowerment for individuals with disabilities. Based on the data studied, it can be concluded that people with disabilities in the Riau Islands Province are still included in the atypical or abnormal category, because so far they have only received assistance in the form of tools and natural food, they are less empowered to improve their abilities in improving selfcompetence or individuals. Keywords: Empowerment, People with Disabilities, Social Service.